ANALISIS PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena L.) AKIBAT PEMBERIAN DOSIS PUPUK ORGANIK CAIR SABUT KELAPA (Cocos nucifera) DAN PUPUK ANORGANIK - Retno Tri Purnamasari; Sri Hariningsih Pratiwi (BUANA SAINS, 2020)
The aim of this research was to determine the impact of the growth and yield analysis of eggplant due to the dosing of coconut husk liquid organic fertilizer and organic fertilizer. The research was conducted in Krapyakrejo Village, Gadingrejo Village, Gadingrejo District, Pasuruan City with an average rainfall of 1000-1500 mm per year at an altitude of 5 m asl in March-August 2020. The study used a Randomized Block Design consisting of a combination treatment of coconut husk organic fertilizers and inorganic fertilizers, namely: P1 = POC 300 ml + 100% inorganic, P2 = POC 400 ml + 100% inorganic, P3 = POC 500 ml + 100% inorganic, P4 = POC 300 ml + 50% inorganic, P5 = POC ml + 50% inorganic, P6 = POC 500 ml + 50% inorganic each combination was repeated four times. The data obtained from the study were analyzed using analysis of variance (F test), if there is a real or insignificant effect, then it is followed by the BNJ test at the 5% level.The results showed that the impact of giving coconut husk POC had an effect on the analysis of the growth and yield of eggplant. The dosage of POC coconut husk 500 ml+50% inorganic gave higher yields on the growth and yield components. Eggplant plants with a dose of POC coconut husk 500 ml + 50% inorganic produced fresh weight plot-1 of 93,41 kg, and fresh weight of hectare-1 was 71,74 tonnes higher than other treatments.